Chorioptic mange in a flock of goats in Brazil - Pereira, Marcelo de Campos; Traldi, Anneliese de Souza (Brazilian Journal of Veterinary Research and Animal Science, 1991)
The authors report the first finding of Chorioptes bovis parasiting a flock of goats in Brazil. They also add commentaries about the current taxonomic status of the genus and about some of the comparative morphologic features of the two species of choriopticmites found associated with goats until now.